2020
DOI: 10.1101/2020.06.17.156893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA-seq reveals a concomitant delay in differentiation and cell cycle of aged hematopoietic stem cell

Abstract: Hematopoietic stem cells (HSCs) are the guarantor of the proper functioning of hematopoiesis due to their incredible diversity of potential. During aging the heterogeneity of mouse HSCs evolves, which contributes to the deterioration of the immune system. Here we address the transcriptional plasticity of HSC upon aging at the single-cell resolution. Through the analysis of 15,000 young and aged transcriptomes, we reveal 15 clusters of HSCs unveiling rare and specific HSC abilities that change with age. Pseudot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Single-cell RNA sequencing comparing young and aged LSK-SLAM HSCs revealed a lower frequency of cells in the G 1 phase among old compared with young HSCs (Kowalczyk et al, 2015). Another study that analyzed a large number of cells at a deeper resolution and used LSK-SLAM Flt3 − to define LT-HSCs, suggested that aged HSCs have a delay in differentiation caused by cell cycle arrest and imbalance of cell cycle regulators (Hérault et al, 2021). Interestingly, the Nakauchi group reported a subset of HSCs in the aged LSK CD150 + CD41 + CD34 − compartment that exhibited myeloidrestricted repopulating activity in primary recipients acquired lymphoid potential upon secondary transplantation, suggesting the existence of a population of "latent-balanced HSCs" in aged mice (Yamamoto et al, 2018).…”
Section: Hsc Cell Cycling Rate Evolves With Agingmentioning
confidence: 99%
“…Single-cell RNA sequencing comparing young and aged LSK-SLAM HSCs revealed a lower frequency of cells in the G 1 phase among old compared with young HSCs (Kowalczyk et al, 2015). Another study that analyzed a large number of cells at a deeper resolution and used LSK-SLAM Flt3 − to define LT-HSCs, suggested that aged HSCs have a delay in differentiation caused by cell cycle arrest and imbalance of cell cycle regulators (Hérault et al, 2021). Interestingly, the Nakauchi group reported a subset of HSCs in the aged LSK CD150 + CD41 + CD34 − compartment that exhibited myeloidrestricted repopulating activity in primary recipients acquired lymphoid potential upon secondary transplantation, suggesting the existence of a population of "latent-balanced HSCs" in aged mice (Yamamoto et al, 2018).…”
Section: Hsc Cell Cycling Rate Evolves With Agingmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors noted that Additional file 1 was missing the supplemental Figures S1-S12. The corrected version of Additional file 1 is attached to this Author Correction and the Additional file 1 has been updated in the original article accordingly.…”
mentioning
confidence: 99%